38. Application of lean-six-sigma methodology in radiotherapy: Breast daily repositioning case. (December 2018) - Mancosu, P.; Nicolini, G.; Goretti, G.; De Rose, F.; Franceschini, D.; Ferrari, C.; Reggiori, G.; Stravato, A.; Paganini, L.; Palumbo, V.; Lobefalo, F.; Gaudino, A.; et al.
Abstract : Purpose: The concept of quality assurance in radiotherapy encompasses a comprehensive approach to all activities in the department. When hypo-fractionation regiment is adopted, the need of a continuous quality procedures updating is self-evident. At this aim, the Lean Six Sigma Methodology (LSSM) has been applied. LSSM was introduced in industry for providing near-perfect services to large processes, by reducing improbable occurrence. It consists of the synergetic adoption of two methods: (i) create a continuous process flow eliminating waste (Lean); (ii) reduce process variation (Six sigma). LSSM has been prospectively applied to breast patient repositioning. This is the first time the LSSM has been rigorously applied to a RT process. Methods: Breast patients treated by hypo-fractionated RT in SIB delivered through VMAT technology with daily 2D-2D matching were considered. The five DMAIC (Define, Measure, Analyze, Improve, Control) LSSM steps were applied by an interdisciplinary team. The process was retrospective measured over 30 months (Jul2014–Dec2016) by querying the RT Record&Verify database. Cause&Effect relationships were analyzed, identifying possible failure sources and potential alternatives for reducing the improbable occurrences. The lean instruments were considered for improving the process. The procedure was controlled over 6 months (Gen-Jun 2017). Results: Applied shifts of 14931 consecutive fractions from 1342 patients were analyzed. The major observed discrepancy was the monthly percentage of fractions with Almost Zero Shifts (AZS = 13.2% ± 6.1% – Fig. 1). Ishikawa fishbone diagram helped in defining the main discrepancy con-causes (Fig. 2). Procedure harmonization involving a multidisciplinary team to increase confidence in matching procedure was defined. AZS was reduced to 4.8% ± 0.6%; distribution symmetry improvement (Skewness moved from 1.4 to 1.1) and outlier eduction, verified by Kurtosis diminution, demonstrated better "normalization" of the procedure after the LSSM application. Conclusions: LSSM was successfully applied in a RT department, allowing the breast repositioning matching procedure to be redesigned.